Nominalization in Koro - Sinha, Nupur; Barbora, Madhumita (Investigationes Linguisticae, 2019)
Koro is a Tibeto-Burman language spoken in the East Kameng district of Arunachal Pradesh. The present paper deals with the nominalization processes in Koro. Two types of nominalizing strategy is seen in Koro: derivational and clausal. Derivational nominalization derives a noun from a non-nominal lexical root (a verb or adjective) as [V-NMZ]N or [ADJ-NMZ]N. In clausal nominalizations, the nominalized clause is subordinate to the matrix clause. Koro employs the morphological marker –gõ to derive nouns from action verbs. The clausal nominals do not take any nominalizer marker but display nominal markers like number, definite articles, case on the verb.